Viral Pathogens of the Penaeid Shrimp - Loh, Philip C. (Adv Virus Res, 1997)
While significant advances that have been made in determining the role of viruses involved in various epizootics occurring in penned shrimp aquaculture, viral diseases will continue to plague the industry. A major obstacle to the study of these diseases is the lack of convenient and quantitative methodologies, such as in vitro cell culture systems to grow and study (characterize) the virus. A beginning has been made with the recent development of protocols for the consistent preparation of primary shrimp lymphoid cells, which were employed for the quanta1 assay of some of the shrimp viral pathogens. The primary cell lines have also been used to analyze the synthesis of viral proteins at the cellular level and to study viral pathogenesis. With the further successful development of additional primary cell lines from other shrimp tissues and the establishment of continuous diploid and transformed shrimp cell lines, this problem is being solved. The value of cell culture systems is becoming increasingly clear. They present several obvious advantages because (1) they are more cost effective, sensitive, and convenient than whole animals, particularly for rapid monitoring of infectivity, (2) they yield quantitatively reproducible results, and (3) viral growth kinetics, biochemical and genetic characteristics, and so on can be studied more easily. Their biggest potential use is in future molecular biology and genetic studies of shrimp viruses.